Cocaine-induced 'active immobility' and its modulation by the serotonin1A receptor. - Müller, C; Thönnessen, H; Jocham, G; Barros, M; Tomaz, C; Carey, R; Huston, J (2004)
'Active immobility' (AI) is an independent behaviour that can be characterized by behavioural immobility, an increased muscular rigidity and the sustaining of an unusual posture. In previous studies with cocaine we observed, concomitant with hyperlocomotion and increased rearing activity, an increase in AI in well-habituated animals, which may constitute another 'positive' acute effect of cocaine on behaviour. The contribution of the serotonergic (5-HT) system to AI is well established. However, little information exists about the contribution of particular 5-HT-receptor subtypes. In order to examine a possible role of the 5-HT1A receptor on this effect of cocaine, we systematically re-analysed four previous experiments in well-habituated animals and one in little-habituated animals, focusing on the acute behavioural effects of cocaine on AI. We found that, in well-habituated animals, cocaine at a medium dose (10 mg/kg, i.p.) induces AI behaviour, which, however, does not correlate with cocaine effects on locomotion, rearing or grooming behaviour. However, there was no effect of cocaine (1, 5 or 15 mg/kg, i.p.) on AI in little-habituated animals. The 5-HT1A-receptor antagonist, WAY 100635 [N-[2-(4-2-methoxyphenyl)-1-piperazinyl]ethyl]-N-(2-pyridinyl) cyclohexane carboxamide trihydrochloride] (0.4 mg/kg, i.p.), potentiated cocaine-induced AI in well-habituated animals, while the 5-HT1A-receptor agonist, 8-OH-DPAT (0.2 mg/kg, i.p.), attenuated it. The local application of 8-OH-DPAT [8-hydroxy-2-(di-n-propylamino)tetralin] into the nucleus accumbens (0, 1, 10 micromol/l) or hippocampus (0, 0.1, 1, 10 micromol/l) modulated cocaine-induced AI in a complex way. These results showed that cocaine induces AI at a medium dose in well-habituated but not in little-habituated animals. The cocaine-induced AI in well-habituated animals can be potentiated by systemic 5-HT1A-receptor antagonism and attenuated by 5-HT1A-receptor agonism. Two experiments with local activation of postsynaptic 5-HT1A receptors revealed that both nucleus accumbens and hippocampal 5-HT1A-receptor populations are involved in the expression of cocaine-induced AI.